Diazotroph diversity and nitrogen fixation in the coral Stylophora pistillata from the Great Barrier Reef. Issue 3 (March 2018) - Lesser, Michael; Morrow, Kathleen; Pankey, Sabrina; Noonan, Sam
Abstract Diazotrophs, both Bacteria and Archaea, capable of fixing nitrogen (N2 ), are present in the tissues and mucous, of corals and can supplement the coral holobiont nitrogen budget with fixed nitrogen (N) in the form of ammonia (NH3 ).Stylophora pistillata from Heron Island on the Great Barrier Reef collected at 5 and 15 m, and experimentally manipulated in the laboratory, showed that the rates of net photosynthesis, steady state quantum yields of photosystem II (PSII) fluorescence (∆F v /F m ′) and calcification varied based on irradiance as expected. Rates of N2 fixation were, however, invariant across treatments while the amount of fixed N contributing toSymbiodinium spp. N demand is irradiance dependent. Additionally, both theSymbiodinium and diazotrophic communities are significantly different based on depth, and novel Cluster VnifH gene phylotypes, which are not known to fix nitrogen, were recovered. A functional analysis using PICRUSt also showed that shallow corals were enriched in genes involved in nitrogen metabolism, and N2 fixation specifically. Corals have evolved a number of strategies to derive nitrogen from organic (e.g., heterotrophic feeding) and inorganic sources (e.g., N2 fixation) to maintain critical pathways such as protein synthesis to succeed ecologically in nitrogen-limited habitats.